2015
DOI: 10.1111/bcp.12678
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–effect relationship of mycophenolic acid and prednisolone in adult patients with lupus nephritis

Abstract: AIMSThe aim was to examine relationships between total and unbound mycophenolic acid (MPA) and prednisolone exposure and clinical outcomes in patients with lupus nephritis. METHODSSix blood samples were drawn pre-and at 1, 2, 4, 6 and 8 h post-dose and total and unbound MPA and prednisolone pre-dose (C 0 ), maximum concentration (C max ) and area under the concentration-time curve (AUC) were determined using non-compartmental analysis in 25 patients. The analyses evaluated drug exposures in relation to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Moreover, high between-patient variability in MPAshortened AUC was observed with extremes of 5.69 and 50.05 μg•h/mL•g (CV% of 53.5%) as well as 37.97 and 590.5 ng•h/mL•g (CV% of 63.8%) for dose-normalized total and free MPA AUC 0-2 , respectively. It is in accordance with other pharmacokinetic studies carried out in LN [2,7,20]. Recently, Abd Rahman et al [2] reported CV% of 50% and 53% for dose-normalized total and free MPA AUC 0-12 , Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, high between-patient variability in MPAshortened AUC was observed with extremes of 5.69 and 50.05 μg•h/mL•g (CV% of 53.5%) as well as 37.97 and 590.5 ng•h/mL•g (CV% of 63.8%) for dose-normalized total and free MPA AUC 0-2 , respectively. It is in accordance with other pharmacokinetic studies carried out in LN [2,7,20]. Recently, Abd Rahman et al [2] reported CV% of 50% and 53% for dose-normalized total and free MPA AUC 0-12 , Fig.…”
Section: Discussionsupporting
confidence: 90%
“…According to our knowledge, there have been two studies so far which evaluated not only total but also free MPA pharmacokinetics in adult LN patients [2,11]. However, our report presents research that additionally examined relationship between free and total MPA concentration-related parameters in this particular population of patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Median as well as mean dose-normalized values of MPA C trough and AUC 0-12 in our study were similar or slightly higher than in adult renal transplant recipients (Engelbertink et al, 2002;Kuypers et al, 2003;Shaw et al, 2004;Tedesco-Silva et al, 2005). On the other hand, median and mean dose-normalized MPA C trough and AUC 0-12 in our study were higher than those obtained in patients with lupus nephritis (Abd Rahman et al, 2015;Alexander et al, 2014).…”
Section: Discussionsupporting
confidence: 66%